Employee Job Satisfaction: An Analysis of Key Determinants - Acharya, Chandrika; Pokharel, Ashok; Ranjitkar, Rojina (United Journal of Interdisciplinary Studies, 2024)
Employee job satisfaction is crucial for organizational success and employees’ well-being, as it influences engagement, retention, and overall productivity. Maslow’s hierarchy of needs provides a comprehensive framework for understanding the factors that contribute to job satisfaction, including physiological, safety, social, esteem, and self-actualization needs. This study aims to examine the determinants of employee job satisfaction within this framework, focusing on teaching staff in the United Academy Group (UAG), comprising of United Pre-School, United School, United Universal School, United Academy, and United College. Utilizing a quantitative research approach and correlational design, data were collected through questionnaires distributed to 161 teachers from various institutions within the UAG. This study found that basic needs and social needs significantly impact job satisfaction, while safety and esteem needs do not show significant associations. Interestingly, self-actualization needs also emerged as a significant determinant of job satisfaction, highlighting the importance of personal growth and fulfillment in the workplace. Therefore, utilizing Maslow's hierarchy of needs as a framework, organizations should prioritize fostering environments that address basic and social needs while also nurturing opportunities for personal growth and self-actualization to enhance employee job-satisfaction and overall well-being.